Bridging the gap in maritime archaeology : working with professional and public communities - Bell, Katy, (Access archaeology., 2019)
Proceedings of a conference session held at CIfA 2014. The session focused on ways in which it is possible to engage with a wider audience in the course of maritime archaeological work. Papers offer a series of case studies exhibiting best practice with regard to individual maritime projects and examples of outreach to local communities.